2007
DOI: 10.1093/jmedent/44.4.666
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation ofMusca domestica(Diptera: Muscidae) as a Vector of Newcastle Disease Virus

Abstract: House flies, Musca domestica L. (Diptera: Muscidae), were examined for their ability to harbor and transmit Newcastle disease virus (family Paramyxoviridae, genus Avulavirus, NDV) by using a mesogenic NDV strain. Laboratory-reared flies were experimentally exposed to NDV (Roakin strain) by allowing flies to imbibe an inoculum consisting of chicken embryo-propagated virus. NDV was detected in dissected crops and intestinal tissues from exposed flies for up to 96 and 24 h postexposure, respectively; no virus was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…The swab samples collected from transfer containers contained a maximal CN of 10 5 SARS-CoV-2 RNA/µl, indicating that house flies carry RNA amounts which are on the borderline for containing infectious virus to be detected in our VI assay. A similar observation was made in an another study involving house fly transmission of Newcastle disease virus [ 16 ], where house flies harbored an insufficient amount of virus to transmit the pathogen.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The swab samples collected from transfer containers contained a maximal CN of 10 5 SARS-CoV-2 RNA/µl, indicating that house flies carry RNA amounts which are on the borderline for containing infectious virus to be detected in our VI assay. A similar observation was made in an another study involving house fly transmission of Newcastle disease virus [ 16 ], where house flies harbored an insufficient amount of virus to transmit the pathogen.…”
Section: Discussionsupporting
confidence: 77%
“…wings, legs, mouthparts) and internally in their alimentary canal [ 13 , 14 ]. Moreover, house flies have been demonstrated to transmit coronaviruses, namely the turkey coronavirus (TCV) [ 15 ], and other important viral agents, including Newcastle disease virus [ 16 ], porcine respiratory syndrome virus [ 17 ] and porcine transmissible gastroenteritis [ 18 ]. However, the potential for house flies to acquire, harbor and transmit SARS-CoV-2 has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of possible hosts suggests that SARS-CoV-2 could indeed infect a broad range of mammals, and thereby more high-quality epidemiological surveillance studies are much needed. Furthermore, the need for more in-depth research has also increased due to the current lack of studies assessing the mechanical transmission of SARS-CoV-2 by rodents, insects, and arachnids, which have been already recognized as a mechanical vector of over 100 pathogens including bacteria, fungi, virus, and parasites ( El-Sherbini and Gneidy, 2012 ; Foil and Gorham, 2000 ; Gough and Jorgenson, 1983 ; Graczyk et al, 2005 ; Issa, 2019 ; Nayduch and Burrus, 2017 ; Onwugamba et al, 2018 ; Pitkin et al, 2009 ; Watson et al, 2007 ). Although SARS-CoV and other related coronaviruses have been reported to be mechanically transmitted by pests, together with SARS-CoV-2’s survivability on surfaces and in feces for elongated periods would undoubtedly implicate them as culprits in the role of its transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic viruses (Calibeo-Hayes et al, 2003;Chakrabarti et al, 2008;Otake et al, 2004;Schurrer et al, 2005;Watson et al, 2007) bacteria (Ahmad et al, 2011;Doud et al, 2014;Fleming et al, 2014;Goush et al, 2014;Soheyliniya and Barin, 2014;Wei et al, 2014) and parasites (Balla et al, 2014;Graczyk et al, 2005;Szostakowska et al, 2004) have been found on flies. Antibiotic-resistant bacteria were also isolated from flies (Ahmad et al, 2011;Wei et al, 2014).…”
Section: Flies Carry Infectious Diseasesmentioning
confidence: 99%